1998
DOI: 10.1055/s-2008-1034944
|View full text |Cite
|
Sign up to set email alerts
|

Choroidales Infiltrat auf dem Boden eines Myelodysplastischen Syndroms

Abstract: To the best of our knowledge this is the first patient with a choroidal infiltration as the initial sign of progression of myelodysplastic syndrome to acute myeloic leukemia. Realizing this possibility helps for an early diagnosis and rapid therapy which is so crucial in prolonging life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Serous retinal detachment is an uncommon presentation of new or relapsed leukemic disease, but it has been previously reported in cases of ALL and AML in the adult population. In the majority of reported cases of serous retinal detachment or choroidal infiltration, the systemic disease had been diagnosed prior to the development of ocular symptoms [3,4,5,6,7,8,9]. A review of the literature revealed only 5 cases of decreased vision and serous retinal detachment as initial presenting signs of new leukemia in an adult patient [10,11,12,13,14].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Serous retinal detachment is an uncommon presentation of new or relapsed leukemic disease, but it has been previously reported in cases of ALL and AML in the adult population. In the majority of reported cases of serous retinal detachment or choroidal infiltration, the systemic disease had been diagnosed prior to the development of ocular symptoms [3,4,5,6,7,8,9]. A review of the literature revealed only 5 cases of decreased vision and serous retinal detachment as initial presenting signs of new leukemia in an adult patient [10,11,12,13,14].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“… 1 2 It has been reported that leukemias are associated with choroidal infiltration. 12 13 14 Additionally, amaurosis fugax is has been reported in some ET patients that may be due episodic choroidal ischemic attacks. 3 Hence, ET may affect choroidal thickness.…”
Section: Discussionmentioning
confidence: 99%